2021
DOI: 10.3390/ijms22189951
|View full text |Cite
|
Sign up to set email alerts
|

Downregulated TNF-α Levels after Cryo-Thermal Therapy Drive Tregs Fragility to Promote Long-Term Antitumor Immunity

Abstract: Immunotherapy has emerged as a therapeutic pillar in tumor treatment, but only a minority of patients get benefit. Overcoming the limitations of immunosuppressive environment is effective for immunotherapy. Moreover, host T cell activation and longevity within tumor are required for the long-term efficacy. In our previous study, a novel cryo-thermal therapy was developed to improve long-term survival in B16F10 melanoma and s.q. 4T1 breast cancer mouse models. We determined that cryo-thermal therapy induced Th1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Recent studies reveal that combinatorial immunotherapies can exert an antitumor effect by promoting Treg fragility, which characterizes as impaired suppressive function and enhancing partial molecule expression of the Th1 subset, such as high expression of IFN-γ and T-bet ( 19 ). In our previous study, we also found that cryo-thermal therapy could drive the fragility of Tregs, and these Th1-like Tregs downregulated the expression of inhibitory molecules ( 11 ). After combination therapy, higher levels of T-bet and IFN-γ in Tregs were observed ( Supplementary Figure 2 ).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Recent studies reveal that combinatorial immunotherapies can exert an antitumor effect by promoting Treg fragility, which characterizes as impaired suppressive function and enhancing partial molecule expression of the Th1 subset, such as high expression of IFN-γ and T-bet ( 19 ). In our previous study, we also found that cryo-thermal therapy could drive the fragility of Tregs, and these Th1-like Tregs downregulated the expression of inhibitory molecules ( 11 ). After combination therapy, higher levels of T-bet and IFN-γ in Tregs were observed ( Supplementary Figure 2 ).…”
Section: Resultsmentioning
confidence: 93%
“…The 4T1 breast cancer cell line was provided by Shanghai First People’s Hospital, China, and the female BALB/c mice were obtained from Shanghai Slaccas Experimental Animal Co., Ltd. (Shanghai, China). Tumors were established by subcutaneous injection of 4T1 cells (4 × 10 5 cells in 100 μl of phosphate-buffered saline (PBS)) in the right flank of wild-type BALB/c mice as above ( 11 ). All animal experiments were approved by the Animal Welfare Committee of Shanghai Jiao Tong University, and experimental methods were performed in accordance with the guidelines of Shanghai Jiao Tong University Animal Care (approved by Shanghai Jiao Tong University Scientific Ethics Committee, Proto code 2020017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Greatly enhanced immune effects have been discovered through combined cryoablation and thermal therapy [ 69 , 146 , 147 , 148 , 149 ]. Such combined therapy could create an inflammatory environment for stimulation of T cell activation and differentiation, and thus promoting long-term antitumor immunity through inducing the release of tumor-related DAMPs, especially tumor-related HSP70 in situ and the peripheral [ 150 ], down-regulating TNF- levels [ 151 ], and releasing iron [ 152 ]. The synergetic effects are also shown as induced tumor-related DAMPs improving the thermal sensitivity and decreasing the lethal dosage of thermal therapy.…”
Section: Combined Multi-therapiesmentioning
confidence: 99%
“…Moreover, it stimulated a durable antitumor immune response by releasing large amounts of tumor neoantigens and damage-associated molecular patterns (DAMPs) [ 20 , 21 ]. Cryo-thermal therapy could improve the long-term survival of tumor-bearing mice, but the survival rate of the breast cancer-bearing mice was only approximately 50% [ 22 ], which was significantly lower than that of the B16F10 melanoma-bearing mice (approximately 80%) [ 20 ]. 4T1 cells share many molecular features with human triple-negative breast cancer [ 23 ], which is highly aggressive and metastatic [ 24 ].…”
Section: Introductionmentioning
confidence: 99%